Synthesis of highly dispersed Pt nanoclusters anchored graphene composites and their application for non-enzymatic glucose sensing. (1st March 2015) - Chang, Gang; Shu, Honghui; Huang, Qiwei; Oyama, Munetaka; Ji, Kai; Liu, Xiong; He, Yunbin
Highlights: PtNCs/graphene (PVP) composites were obtained by a clean and facile method. The addition of graphene effectively promotes the catalytic performance of composites. The highly dispersed PtNCs show superior electrocatalytic activity to glucose oxidation. PtNCs/graphene (PVP) composites exhibit excellent stability and selectivity for nonenzymatic glucose detection. Abstract: A facile and clean method by using ascorbic acid as mild reductant was developed to synthesize nanocomposites of graphene and platinum nanoclusters (PtNCs/graphene), in which Polyvinyl-Pyrrolidone (PVP) was added during the one-step reductive process so as to improve the dispersity of PtNCs on the graphene and decrease the size of PtNCs. By several characterization methods such as X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS), we demonstrated that Pt nanoclusters have successfully anchored on the surface of graphene sheets with average diameter of 22 nm. It was found that with the assistant of PVP, Pt nanoclusters appeared with smaller particle size and narrower particle size distribution. Cyclic voltammetry and amperometric methods were used to evaluate the electro-catalytic activity of the synthesized nanocomposites toward the oxidation of glucose in neutral media (0.1 M PBS, pH 7.4). The PtNCs/graphene exhibited a rapid response time (about 3 s), a broad linear range (1 mM to 25 mM), good stability, and sensitivity estimated to be 1.21 μA cm −2  mM −1 (R = 0.995, 71.9 μA cm −2  mM −1 vs. geometric area). Additionally, the impact from the oxidation of interferences can be effectively limited by choosing the appropriate detection potential. These results indicated a great potential of PtNCs/graphene in fabricating novel non-enzymatic glucose sensors with high performance.